(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The purpose of this study was to compare the frequency and nature of pain between the vital inflamed (n=55) and non-vital (n=55) teeth that received single visit root canal treatment. The frequency and nature of pain were assessed as no pain, mild, moderate and severe pain on day 2 and day 7. The results showed that 76.4 and 85.5% participants felt no pain in vital inflamed teeth on day 2 and day 7, respectively. On the other hand, 63.6 and 74.5% participants felt no pain in non-vital teeth on day 2 and day 7, respectively. The remaining participants only felt mild to moderate pain. There were no significant difference between the two groups (p=0.435 on day 2 and p=0.371 on day 7). The results suggested that single visit root canal treatment is equally effective in both vital inflamed and non-vital teeth.